Clinical helminth infections alter host gut and saliva microbiota. - Geoffrey N Gobert; Louise E Atkinson; Andrea Lokko; Tippayarat Yoonuan; Orawan Phuphisut; Akkarin Poodeepiyasawat; Nirundorn Homsuwan; Angela Mousley; Poom Adisakwattana (Public Library of Science (PLoS), 2022)
Background Previous reports show altered gut bacterial profiles are associated with helminth infected individuals. Our recently published molecular survey of clinical helminthiases in Thailand border regions demonstrated a more comprehensive picture of infection prevalence when Kato Katz microscopy and copro-qPCR diagnostics were combined. We revealed that Opisthorchis viverrini, hookworm, Ascaris lumbricoides and Trichuris trichiura were the most predominant helminth infections in these regions. In the current study, we have profiled the faecal and saliva microbiota of a subset of these helminth infected participants, in order to determine if microbial changes are associated with parasite infection. Methods A subset of 66 faecal samples from Adisakwattana et al., (2020) were characterised for bacterial diversity using 16S rRNA gene profiling. Of these samples a subset of 24 participant matched saliva samples were also profiled for microbiota diversity. Sequence data were compiled, OTUs assigned, and diversity and abundance analysed using the statistical software Calypso. Results The data reported here indicate that helminth infections impact on both the host gut and oral microbiota. The profiles of faecal and saliva samples, irrespective of the infection status, were considerably different from each other, with more alpha diversity associated with saliva (p-value≤ 0.0015). Helminth infection influenced the faecal microbiota with respect to specific taxa, but not overall microbial alpha diversity. Conversely, helminth infection was associated with increased saliva microbiota alpha diversity (Chao 1 diversity indices) at both the genus (p-value = 0.042) and phylum (p-value = 0.026) taxa levels, compared to uninfected individuals. Elevated individual taxa in infected individuals saliva were noted at the genus and family levels. Since Opisthorchis viverrini infections as a prominent health concern to Thailand, this pathogen was examined separately to other helminths infections present. Individuals with an O. viverrini mono-infection displayed both increases and decreases in genera present in their faecal microbiota, while increases in three families and one order were also observed in these samples. Discussion In this study, helminth infections appear to alter the abundance of specific faecal bacterial taxa, but do not impact on overall bacterial alpha or beta diversity. In addition, the faecal microbiota of O. viverrini only infected individuals differed from that of other helminth single and dual infections. Saliva microbiota analyses of individuals harbouring active helminth infections presented increased levels of both bacterial alpha diversity and abundance of individual taxa. Our data demonstrate that microbial change is associated with helminthiases in endemic regions of Thailand, and that this is reflected in both faecal and saliva microbiota. To our knowledge, this is the first report of an altered saliva microbiota in helminth infected individuals. This work may provide new avenues for improved diagnostics; and an enhanced understanding of both helminth infection pathology and the interplay between helminths, bacteria and their host.